ANALYSIS OF THE EFFECT OF NATURAL FACTORS ON THE POTENTIAL OF FLOOD AND LANDSLIDE IN THE EAST JEMBER - Vika Aurely Nalurita; Fahmi Arif Kurnianto; Bejo Apriyanto; Y. Yushardi (DEPARTMENT OF GEOGRAPHY EDUCATION, UNIVERSITY OF JEMBER, 2020)
Natural phenomena of floods and landslides are natural phenomena that often occur anywhere and anytime, with these phenomena certainly having negative impacts such as on health and socio-economic conditions. The purpose of this study was to determine the effect of natural factors on the potential for flooding and landslides in the eastern part of Jember. The method used in this study is a qualitative descriptive method because in this study it is based on map and image interpretation techniques (Surface Analysis) while the qualitative method itself is carried out using interpretation elements such as patterns, textures, associations, hues, and also shapes. land. The parameters used in determining the factors prone to flooding and landslides, The research was conducted in several sub-districts, namely Sumberjambe District, Ledokombo District, Silo District, Mayang District, Mumbulsari District and Tempurejo District. In the eastern part of Jember, if seen from the morphology, it is dominated by highlands because in some of these areas it is part of the area at the foot of Mount Raung so that there is a lot of volcanic land, besides that in the eastern part of Jember, it is also dominated by flat land so that it is very possible for natural phenomena to occur. floods and landslides. Geologically, the eastern part of Jember is dominated by lava breccia, tuff and tuff sandstones, lava, volcanic breccias, claystone with siltstone inserts, and sandstone whose ages range from quarter to tertiary age. Silo District, Mayang District, Mumbulsari District and Tempurejo District. In the eastern part of Jember, if seen from the morphology, it is dominated by highlands because in some parts of this area it is part of the area at the foot of Mount Raung so that there is a lot of volcanic land, besides that in the eastern part of Jember, it is also dominated by flat land so that it is very possible for natural phenomena to occur. floods and landslides. Geologically, the eastern part of Jember is dominated by lava breccia rocks, tuff and tuff sandstones, lava, volcanic breccias, claystone with siltstone inserts, and sandstone whose ages range from quarter to tertiary age. Silo District, Mayang District, Mumbulsari District and Tempurejo District. In the eastern part of Jember, if seen from the morphology, it is dominated by highlands because in some parts of this area it is part of the area at the foot of Mount Raung so that there is a lot of volcanic land, besides that in the eastern part of Jember, it is also dominated by flat land so that it is very possible for natural phenomena to occur. floods and landslides. Geologically, the eastern part of Jember is dominated by lava breccia rocks, tuff and tuff sandstones, lava, volcanic breccias, claystone with siltstone inserts, and sandstone whose ages range from quarter to tertiary age. In the eastern part of Jember, if seen from the morphology, it is dominated by highlands because in some parts of this area it is part of the area at the foot of Mount Raung so that there is a lot of volcanic land, besides that in the eastern part of Jember, it is also dominated by flat land so that it is very possible for natural phenomena to occur. floods and landslides. Geologically, the eastern part of Jember is dominated by lava breccia rocks, tuff and tuff sandstones, lava, volcanic breccias, claystone with siltstone inserts, and sandstone whose ages range from quarter to tertiary age. In the eastern part of Jember, if seen from the morphology, it is dominated by highlands because in some of these areas it is part of the area at the foot of Mount Raung so that there is a lot of volcanic land, besides that in the eastern part of Jember, it is also dominated by flat land so that it is very possible for natural phenomena to occur. floods and landslides. Geologically, the eastern part of Jember is dominated by lava breccia, tuff and tuff sandstones, lava, volcanic breccias, claystone with siltstone inserts, and sandstone whose ages range from quarter to tertiary age. In addition, the eastern part of Jember is also dominated by flat land so that it is very possible for natural phenomena to occur as floods and landslides. Geologically, the eastern part of Jember is dominated by lava breccia, tuff and tuff sandstones, lava, volcanic breccias, claystone with siltstone inserts, and sandstone whose ages range from quarter to tertiary age. In addition, the eastern part of Jember is also dominated by flat land so that it is very possible for natural phenomena to occur as floods and landslides. Geologically, the eastern part of Jember is dominated by lava breccia, tuff and tuff sandstones, lava, volcanic breccias, claystone with siltstone inserts, and sandstone whose ages range from quarter to tertiary age.